Modeling and balancing of HVAC air duct systems - Chen, Haoran (2016)
This thesis presents the development of new tools for duct system simulation and advanced techniques for air balancing that methodically proportion the air flows through the duct system mains, branches and terminal devices, based on computational model of duct system. The new simulation tools based on differential algebraic equation solver is efficient and convenient for duct system modelling, analysis, identification and optimization. The new air balancing methods are non-iterative, efficient, easy to use and accurate, which overcome the disadvantages of traditional methods that are based on rules of thumb, inaccurate, time-consuming and costly. The contributions of this thesis include: 1. Develop the duct system model using circuit network analogy based on the pressure drop relationships of the conduits and fittings. Implement a powerful and easy-to-use block library in MATLAB/Simulink environment using Simscape physical modeling language simulation. Define a class for the duct model simulation for professional high-performance applications with flexible application programming interface. The duct model could be used to perform duct system simulation accurately with high flexibility and scalability. 2. Propose a non-iterative air balancing method, which is accurate, efficient and simple to operate. The method is implemented by three steps: 1) adjust dampers and collect measurements of pressures and flow rates; 2) identify the parameters of the duct model using the obtained data; 3) calculate the optimal damper positions corresponding to the balanced flow distribution while minimizing the fan energy consumption. A sequential damper adjustment guide using flow measurements as the indicator is proposed in case of inaccurate damper position indicator. This method requires only common measuring devices, so it is suitable for unprofessional users in balancing small to intermediate HVAC systems. 3. Establish a fan-independent air balancing method which modifies model formulation, data acquisition, parameter identification, and adjusting operations for improved accuracy and robustness. In this method, the fan outlet pressure is monitored by a pressure sensor. The duct model and the parameter identification algorithm is modified to estimate both duct parameters and pressures simultaneously. After obtaining the balanced damper positions, a novel indicator considering the variations of fan pressures is introduced for sequential adjustment of dampers. This method is more accurate and robust against modeling error and disturbances of fans. The extra cost is acceptable given the significant performance improvement. This method is suitable for high performance applications where more accurate airflow distribution is required.